Investigation on electrically conductive aggregates as grounding using activated carbon and pyrolytic carbon - Tengku Hafidatul Husna, Tengku Anuar (2019)
Electrical earthing system main purpose is to disperse flow of charge to mother earth within the shortest time possible at the event of lightning or fault. Earth grounding assists a lightning-protection in industrial and power plants. Thus, there have been several studies on several materials in order to find the best performing materials for an earthing system. Activated carbon and pyrolytic carbon are used to improve the performance of earth grounding system. The study aims to determine the physical properties and characteristic of materials, establish carbon water retention curve at varying percentage of water content as well as identify the electrical resistivity, water absorption and crushing strength. Two carbon were used in this study namely, activated carbon and pyrolytic carbon. These materials were tested under powder and aggregated form. The samples carbon water retention curve (CWRC) was established by WP4C and electrical resistivity were studied by using soil box method. The effects of activated carbon and pyrolytic carbon on electrical resistivity, water absorption and crushing strength were studied. For activated carbon, at days 28 exhibited 228.6 Ω.m electrical resistivity, 12.11% water absorption and 10.31 N/mm2 crushing strength. Morever, the effect of pyrolytic carbon at days 28 exhibit 218 Ω.m electrical resistivity, 13.27% water absorption and 10.26 N/mm2 crushing strength. Lastly, activated carbon and pyrolytic carbon can be used as an alternative material as ground enhancement material. Comparison for both materials, pyrolytic carbon performed better that activated carbon under all testing conditions. Overall, pyrolytic carbon in powder form outperformed the aggregated form.